GANGGUAN BERBAHASA - Muzaiyanah Muzaiyanah (Wardah, 2014)
Language disorders (Disabilities) can be broadly divided into two. First, disturbances due to medical factors; and secondly due to medical sosial. environmental factors are a nuisance, either due to abnormalities of brain function as well as due to abnormalities of the tools spoken.  Social environment factor is the environment that is not a natural human life, such as marginalized or isolated from the environment of human community life speaking as usual. Speech disorders can be divided into three groups, namely (1) impaired speech, (2) language disorders, and (3) thought disorder.